1997
DOI: 10.1128/iai.65.1.305-308.1997
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Mycobacterium tuberculosis in tight vacuoles in vivo in lung macrophages of mice infected by the respiratory route

Abstract: Following aerosol infection of mice with Mycobacterium tuberculosis, single mycobacteria or pairs of bacilli were observed within individual phagocytic vacuoles bound by tightly apposed vacuolar membranes. The virulent organism was not observed free in the cytoplasm of the parasitized cells or in the extracellular space of the lung granulomata. This study indicates that in vivo, virulent mycobacteria survive and probably replicate within a unique tight vacuole in the infected phagocyte within the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…It is unclear why the methylcitrate cycle is required for growth of M. tuberculosis in murine bone marrow-derived macrophages ex vivo but not in the lungs of mice, where virtually all of the bacteria are located inside macrophages (Moreira et al, 1997). This paradox might be due to differences in the composition of fatty acid pools in bone marrow-derived macrophages versus pulmonary macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why the methylcitrate cycle is required for growth of M. tuberculosis in murine bone marrow-derived macrophages ex vivo but not in the lungs of mice, where virtually all of the bacteria are located inside macrophages (Moreira et al, 1997). This paradox might be due to differences in the composition of fatty acid pools in bone marrow-derived macrophages versus pulmonary macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A minimal epitope (VESTAGSL; CFP10 [32][33][34][35][36][37][38][39] ) was identified that is presented by H-2K k to CD8 ϩ T cells primed during infection. From the same peptide library, a second epitope was identified (LAQEAGNFERISGDL; CFP10 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] ) that is recognized by CD4 ϩ T cells. Both the CD4 ϩ and CD8 ϩ T cell responses to CFP10 evolved similarly in the spleen, lung, and draining LNs of infected C3H/HeJ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Purified CD4 ϩ or CD8 ϩ T cells were cultured with the individual peptides and naive irradiated syngeneic splenocytes, and after 48 h, the culture supernatants were assayed for IFN␥ as a measure of T cell activation. Peptide 3 (LAQEAGNFERIS-GDL; herein referred to as CFP10 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] ) was recognized by CD4 ϩ T cells and the overlapping peptides 7 (amino acid [aa] 27-39: TQIDQVESTAGSL) and 8 (aa 30-44: DQVESTAGSLQGQWR) were recognized by CD8 ϩ T cells from C3H mice, but not B6 or BALB/c mice ( Fig. 1).…”
Section: Cfp10-specific Mhc Class I-restricted Cd8 ϩ T Cells Arementioning
confidence: 99%
See 2 more Smart Citations